The Influence of Self-Concept on Deviant Behaviuor in the Students of Ternate State Islamic Institute - Nur Rahmah Asnawi; Sattu Alang; Ulfiani Rahman; Marjuni Marjuni; Agus Agus (Madrasah Tsanawiyah DDI Cilellang, 2020)
The purpose of this study was to analyze the influence of self-concept on deviant behaviour in the students of Ternate State Islamic Institute. The scope was limited to three problems, they were: 1) Self-concept of students of Ternate State Islamic Institute. 2) The deviant behaviour of students of the Ternate State Islamic Institute. 3) The significance level of self-concept influence on student's deviant behaviour at the Ternate State Islamic Institute. This type of research was field research with a survey approach and psychological sampling technique by using a sampling quota of 77 people. The research instruments were questionnaire and documentation. The analysis techniques were descriptive and inferential statistical techniques. The results showed that: 1) the students' self-concept of Ternate State Islamic Institute was in the medium category, it was 57%. 2) The students' deviant behaviour of Ternate State Islamic Institute was in a low category, it was 8%. Self-concept has a significant effect on deviant behaviour among students of Ternate State Islamic Institute which was14.5%.